2013
DOI: 10.1177/8756087913494083
|View full text |Cite
|
Sign up to set email alerts
|

Influence of maleic anhydride-grafted polyethylene compatibiliser on the tensile, oxygen barrier and thermal properties of rice husk and nanoclay-filled low-density polyethylene composite films

Abstract: Rice husk and nanoclay (montmorillonite)-filled low-density polyethylene composite films were prepared by extrusion blown film. Maleic anhydride-modified polyethylene was used as compatibiliser in various concentrations ranging from 0 to 8 parts per hundred. X-ray difractograms showed an increase in interlayer spacing of montmorillonite from the use of compatibiliser when compared to the uncompatibilised composites; an increase of 20, 33, 36 and 38% for 2, 4, 6 and 8 parts per hundred, respectively, of maleic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
26
0
2

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 33 publications
(35 citation statements)
references
References 30 publications
4
26
0
2
Order By: Relevance
“…A similar behavior has been reported in the literature for polyethylene films containing pro-oxidant agents [31,32]. On the other hand, the reduction of the deformation at rupture of the HDPE-MA-RH and HDPE-MA-EG-RH composites is attributed to the presence of rice husk particles that render the samples less ductile owing to a reduction of the motility of the polyethylene chains [33]. Moreover, it was confirmed that the HDPE-MA-EG-RH sample showed reduced deformation at rupture when compared to sample HDPE-MA-RH, with statistical differences when subjected to accelerated aging and 90 days of biodegradation, thus demonstrating the effect of UV radiation on the composites under study.…”
Section: Mechanical Propertiessupporting
confidence: 85%
“…A similar behavior has been reported in the literature for polyethylene films containing pro-oxidant agents [31,32]. On the other hand, the reduction of the deformation at rupture of the HDPE-MA-RH and HDPE-MA-EG-RH composites is attributed to the presence of rice husk particles that render the samples less ductile owing to a reduction of the motility of the polyethylene chains [33]. Moreover, it was confirmed that the HDPE-MA-EG-RH sample showed reduced deformation at rupture when compared to sample HDPE-MA-RH, with statistical differences when subjected to accelerated aging and 90 days of biodegradation, thus demonstrating the effect of UV radiation on the composites under study.…”
Section: Mechanical Propertiessupporting
confidence: 85%
“…This agglomeration is because the hydroxyl groups tend to form hydrogen bonds inside the macromolecule itself and between other cellulose macromolecules . This agglomeration of fibers decreases homogeneity of the film and, consequently, its mechanical properties .…”
Section: Resultsmentioning
confidence: 99%
“…RH/MMT hybrid filler, having varying amounts of RH (2, 5, and 7 parts per hundred composite, phc), and 2 wt% MMT, was melt compounded with LDPE in a corotating Brabender ® twin‐screw extruder. MAPE was used as a compatibilizing agent for hydrophobic matrix and hydrophilic fillers, and its amount was held constant at 6 wt% of . A detailed formulation of all the prepared composites is shown in Table .…”
Section: Methodsmentioning
confidence: 99%
“…14,22 For compatibilised nanocomposite film, the comparison of diffraction peak location reveals that peak position moved toward lower 2θ and continued to move as the MAPE and EVA content increased. Adding 3 phc MAPE or 12 phc EVA into LDPE/MMT uncompatibilised system resulted in 32% and 25% improvement in interlayer distances of the MMT.…”
Section: Xrdmentioning
confidence: 99%